Pengelolaan Dana Desa untuk Pengembangan Ekonomi Masyarakat Dalam Sudut Pandang Maqashid Syariah di Desa Kalowang - Alvan Fathony; Moh. Khoirul Iqbal (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Starting in 2015, villages get a new budget source, namely the Village Fund, which comes from the State Revenue and Expenditure Budget (APBN). Each village will receive an additional budget in the form of village funds which will be received in stages. Village funds are calculated based on four factors, namely population size, area size, poverty rate and geographical difficulties. Village funds are prioritized to fund community development and empowerment. Village funds have a very important role in improving the village economy, increasing village income and reducing the number of poor people, including education, health and income. This research is a field research method or field research, namely research on data and information sourced from field data obtained by conducting observations and interviews in Kalowang Village, Gayam District which is then analyzed using the descriptive analysis method using primary and secondary data. The data obtained is processed in such a way thereby providing systematic data. The management of Kalowang village funds is in accordance with the principles of Islamic economics, all of which are packaged in the nature of the prophet, namely by applying the concept of sidiq, right, the basic value is integrity. The values ​​in the economy are in the form of honesty, sincerity, security, emotional balance. Keywords: village funds, economic development, maqashid sharia